2009
DOI: 10.1007/s10637-009-9278-9
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidinyl-arylpropionic acid derivatives: viable resources in the development of new antineoplastic agents

Abstract: Numerous studies have documented that various naturally derived ligands or synthetic non-thiazolidinediones (TZD) as peroxisome proliferator-activated receptor gamma (PPARgamma) agonists have shown moderate or potent antitumor activities, which is PPARgamma independent or partially dependent. However, the PPARgamma agonistic or glucose-lowering activity is ranked first more often than antitumor activity to determine promising novel PPARgamma agonists for potential clinical use. In this study, we hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Since long-term treatment with rosiglitazone is known to cause weight gain, fluid retention, and some of devastating side effects, we have designed and synthesized a new group of PPARγ agonists for the purpose of minimizing the problem. After extensive screening, we have identified DH9 as a candidate which did not cause the weight gain in mice after 21 days of treatment [8]. Comparing with rosiglitazone, DH9 was a much potent inhibitor of ADPKD cell proliferation, with a magnitude of difference of 6-fold over rosiglitazone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since long-term treatment with rosiglitazone is known to cause weight gain, fluid retention, and some of devastating side effects, we have designed and synthesized a new group of PPARγ agonists for the purpose of minimizing the problem. After extensive screening, we have identified DH9 as a candidate which did not cause the weight gain in mice after 21 days of treatment [8]. Comparing with rosiglitazone, DH9 was a much potent inhibitor of ADPKD cell proliferation, with a magnitude of difference of 6-fold over rosiglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, however, we found that DH9 exhibits a stronger anti-tumor activity. DH9 treatment substantially improves general health status and survival and reduces tumor size in multiple-tumors-bearing mice [8].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation